2019
DOI: 10.21608/adjg.2019.42136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear Bond Strength of Self-Adhering Flowable Composite to Mineral Trioxide Aggregate and Biodentine

Abstract: Purpose: This study aimed to evaluate shear bond strength of mineral trioxide aggregate and biodentine to self-adhering flowable composite. Materials and Methods: eighty Double Split Teflon mold has been prepared with a central hole measuring (3mm in diameter and 2 mm in height) for the mold used for tested materials and (2mm in diameter and in height) for the other mold used for restorative material. The molds were filled with MTA and Biodentine. The mixing material MTA and biodentine applied to its mold (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(23 reference statements)
0
4
1
Order By: Relevance
“…There are studies in the literature with different results regarding the μSBS of FC to Biodentine and MTA. 1,[34][35][36] Although the μSBS values for Biodentine were higher than those for MTA according to this study's results, there was no statistically significant difference in the μSBS of FC and acid-etched SARC to BIOfactor MTA. In a study that aimed to evaluate the SBS of a SARC and FC to MTA, Biodentine, and a calciumenriched mixture (CEM), researchers found that the SBS values for MTA were higher than those for Biodentine, and the difference between these materials was statistically insignificant.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…There are studies in the literature with different results regarding the μSBS of FC to Biodentine and MTA. 1,[34][35][36] Although the μSBS values for Biodentine were higher than those for MTA according to this study's results, there was no statistically significant difference in the μSBS of FC and acid-etched SARC to BIOfactor MTA. In a study that aimed to evaluate the SBS of a SARC and FC to MTA, Biodentine, and a calciumenriched mixture (CEM), researchers found that the SBS values for MTA were higher than those for Biodentine, and the difference between these materials was statistically insignificant.…”
Section: Discussioncontrasting
confidence: 45%
“…34 On the contrary, other studies have reported higher SBS values for Biodentine than for MTA. 35,36 In this study, Biodentine had the highest μSBS values in all adhesive strategies. The differences in μSBS were attributed values to the different characteristics of the materials and acid-etching applications.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although there are many studies in the literature investigating the bond strength of direct pulp capping materials to dental adhesives, different and contradictory results have been obtained in the bond strength of capping materials to adhesive resins after different hardening times in different studies. 19,22,30,31 However, there are different factors that can affect the bond strength of composite resins to capping materials in clinical conditions. During the restorative treatments in the clinical conditions, leakage of saliva and blood into the cavity during the different stages of restorative material applications will cause contamination of the surface and pose a risk for the bond strength of the restoration.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Abdel-Rhman et al 31 , it was proposed that MTA provided the desired impermeability after at least 72 hours and recommended waiting for 72 hours before the restoration. It was also reported that although the initial setting reaction of Biodentin takes 12 minutes after mixing powder and liquid, Biodentin gains its full physical properties after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%